2015
DOI: 10.1097/aog.0000000000000921
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Resolution of Auditory Passage of Vaginal Air in Women With Pelvic Floor Disorders

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
(17 reference statements)
0
5
0
1
Order By: Relevance
“…The theory of VL trapping air, thus leading to vaginal wind is plausible. In a study aimed at evaluating this symptom, vaginal wind was found to share many of the VL characteristics uncovered in our study, most importantly its higher prevalence in younger women and the lack of association with POP …”
Section: Discussionmentioning
confidence: 64%
“…The theory of VL trapping air, thus leading to vaginal wind is plausible. In a study aimed at evaluating this symptom, vaginal wind was found to share many of the VL characteristics uncovered in our study, most importantly its higher prevalence in younger women and the lack of association with POP …”
Section: Discussionmentioning
confidence: 64%
“…Functionally, they may struggle with clothing discomfort or dyspareunia in addition to struggles relating to body image or feelings of inadequacy during intimate moments. Patients may also have complaints of vaginal laxity, now defined by the IUGA/ICS as “excessive vaginal looseness,” or have issues with air trapping or vaginal wind resulting in noises emanating from the vagina during activity .…”
Section: External Genitalsmentioning
confidence: 99%
“…Les rapports sexuels étaient en cause dans 54% des cas, sinon les GV survenaient au cours de l'activité physique. Une étude comparative (19) de prévalence des GV chez 110 femmes (âge moyen 55 ans) dont 59 avaient un prolapsus et 51 sans, ne montre aucune différence en présence ou non d'un tel trouble de la statique. La majorité des femmes (87%) expérimentaient ces GV pendant les rapports sexuels avec une gêne chez 64% d'entre elles mais seulement 22% considéraient que ces GV déterminaient une altération de leur qualité de vie.…”
Section: Discussionunclassified